2011
DOI: 10.1109/tvt.2011.2116051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Channel State Prediction Considering Delays in Practical Cognitive Radio

Abstract: Abstract-As a part of the effort toward building a cognitive radio network testbed, we have demonstrated real-time spectrum sensing. Spectrum sensing is the cornerstone of cognitive radio. However, current hardware platforms for cognitive radio introduce time delays that undermine the accuracy of spectrum sensing. The time delay, named response delay, incurred by hardware and software can be measured at two antennas colocated at a secondary user (SU), the receiving antenna and the transmitting antenna. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…These methods include: an approach based on MCs [13,24], the normalised least mean square (NLMS) approach [1,19], the first nearest neighbour approach (1-NN) [10] and a simple sliding occupancy window (OW) based method (proposed by the authors) [7]. These methods will all be compared to a uniformly distributed random prediction process.…”
Section: Prediction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods include: an approach based on MCs [13,24], the normalised least mean square (NLMS) approach [1,19], the first nearest neighbour approach (1-NN) [10] and a simple sliding occupancy window (OW) based method (proposed by the authors) [7]. These methods will all be compared to a uniformly distributed random prediction process.…”
Section: Prediction Methodsmentioning
confidence: 99%
“…A linear regression model for predicting video traffic was proposed in [27] and methods based on adaptive filter theory have been described in [1,19,18]. The concept of combining cooperation amongst SUs with prediction was briefly explored in [10], where it was suggested that a cooperative gain could be obtained if a large number of SUs with diverse channel characteristics could be employed.…”
Section: Traffic Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the estimated statistical model, spectrum occupancy prediction at future instances is achievable. Such models examine several statistical techniques with a major literature focus on Markov processes [10,45], Poisson processes [12,13], Bayesian models [9,14], neural networks [5,11,46], linear regression [15,16], space vector machine [47], pattern mining [48,49], and dictionary-based prediction [9]. In a sequential prediction framework, these techniques represent different parametrised predictor classes.…”
Section: Statistical Occupancy Modellingmentioning
confidence: 99%
“…By predicting the channel status in advance, more processing time is available for spectrum sensing, decisions, and mobility [5]. SOP models address prediction either explicitly [9][10][11] or implicitly. Implicit approaches present SOP models as primary/secondary user activity models.…”
Section: Introductionmentioning
confidence: 99%